FUZZY PARAMETERIZED FUZZY SOFT RINGS AND APPLICATIONS - Liu, Xianping; Zhan, Jianming (Italian Journal of Pure and Applied Mathematics, 2015)
The concepts of FP-fuzzy soft rings, FP-equivalent fuzzy soft rings and FP-increasing (decreasing) fuzzy soft rings are introduced. Then some properties of them are given. Finally, aggregate fuzzy subrings are proposed by aggregate fuzzy sets of FP-fuzzy soft rings.